Sporting reunions, contemporary collections and collective biographies: a case study of Harry Batt's 1971 England team. Issue 2 (3rd April 2019) - Williams, Jean; Compton, Joanna; Scarlett, Belinda
ABSTRACT: This article centres on a reunion held at the National Football Museum in 2018 of women football players active before 1993, particularly the England team for the unofficial Women's World Cup in 1971. After outlining the organisation of the tournament, the experience of the three youngest England players is articulated using oral history case studies. Finally the argument suggests that social strategies, such as reunions, enable a degree of reminiscence therapy and provide museum and archives with potential material, currently in the private domain, to build contemporary collections, provided that players are willing to gift or loan their items.